Mola Recurrent (Clinical and Statistical Study) - Bachmann Sánchez, Carlos (2015)
Statistical study of three clinical cases occurred in Mola Recurrent Maternity Hospital of Lima, during the years 1970-1971, a total of 64.925 children live births and 9,722 incomplete abortions, 134 cases having been filed Hydatidiform done, what giving an incidence of Mola per 485 live births, a 73 abortions per Mola and a Mola Mola 45 Recurrent per mole. The clinical presentation, pathology, diagnosis and treatment is the same as that of the Mola Singular. The present trend Recurrent Mola is eleven times higher in a woman who has had a previous Mola.